1996
DOI: 10.1152/ajpendo.1996.271.2.e284
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid oxidation but normal muscle glycogen response to epinephrine in humans with IDDM

Abstract: The effects of physiological increments in epinephrine and insulin on glucose production (GP), skeletal muscle glycogen metabolism, and substrate oxidation were studied in eight insulin-dependent diabetes mellitus (IDDM) and nine control subjects. Epinephrine was coinfused for the final 120 min of a 240-min euglycemic, hyperinsulinemic clamp. In both groups, insulin increased glucose uptake, glycogen synthesis, and whole body carbohydrate (CHO) oxidation and inhibited GP (by 70-80%) and lipid oxidation (by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…It is suggested that prolonged hyperlipidemia may contribute to the increased production of glucose via increased expression of this protein. Taken together with numerous other reports on the impact of lipids on carbohydrate metabolism in skeletal muscle (7)(8)(9), liver (8)(9)(10)12,13), and pancreatic (3-cells (11,38,39), our finding provides experimental support for the role of hyperlipidemia in the pathogenesis of NIDDM (40,41).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is suggested that prolonged hyperlipidemia may contribute to the increased production of glucose via increased expression of this protein. Taken together with numerous other reports on the impact of lipids on carbohydrate metabolism in skeletal muscle (7)(8)(9), liver (8)(9)(10)12,13), and pancreatic (3-cells (11,38,39), our finding provides experimental support for the role of hyperlipidemia in the pathogenesis of NIDDM (40,41).…”
Section: Discussionsupporting
confidence: 87%
“…It also suggests that the mechanism(s) by which a sustained increase in the availability of lipids might affect hepatic glucose output involves more than the short-term increase in the rate of gluconeogenesis (15). Indeed, increased hepatic glucose production is an early (~1 week) consequence of high-fat feeding in rodents (34), and the plasma FFA levels are closely related to the rate of endogenous glucose production in humans (8)(9)(10)12,13). Furthermore, most patients with NIDDM display increased concentrations of plasma FFA throughout the day (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in non-ketotic states, type 1 diabetics have dyslipidemia, or elevated levels of FFA in serum [17]. Following insulin-induced hypoglycemia, stimulation of type 1 diabetics with epinephrine results in increases in FFA greater than in controls subjected to the same maneuver [18], [19]. Short term ketosis in type 1 diabetics is associated with almost doubled plasma FFA concentrations [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found no differences in response to direct adrenergic stimulation [24,28] or response to hypoglycemic adrenergic counterregulation, whereas others have found significant increases in lipolytic [29] or ketogenic [30] responses to epinephrine infusion or hypoglycemia-induced epinephrine secretion in type 1 diabetes mellitus [31,32]. Differences in metabolic control, method of b-adrenergic stimulation, and metabolic conditions likely account for the differences.…”
Section: Discussionmentioning
confidence: 99%